Development of improved rotor blade tip shape using multidisciplinary design analysis and optimization - Lee, J.; Kang, S.N.; Lee, S.G.; Im, D.K.; Kang, H.J.; Lee, D.J. (My University, 2018)
Tip shape optimization of rotor blade is performed to improve hover performance and to reduce required power and forward flight noise by using multidisciplinary design analysis and optimization framework with ModelCenter. The blade tip above radius of 93.5% is optimized from the Light Civil Helicopter being developed in Korea. The single sweep tip is slightly good at hover performance and forward flight noise. The single sweep tip is superior to approach noise and dynamic load of pitch link in particular. It is inferred that the single sweep tip is the optimal solution. The optimal design is analyzed in noise condition using CSD/CFD coupling method to validate results from MDAO process. The single sweep tip shape has lower noise level than baseline.